Behavior of Hollow Thin Welded Tubes Filled with Sand Slag Concrete - Noureddine Ferhoune; Meriem Senani; Abdelhamid Guettala (Advances in Materials Science and Engineering)
This paper presents the axial bearing capacity of thin welded rectangular steel stubs filled with concrete sand. A series of tests was conducted to study the behavior of short composite columns under axial compressive load; the cross section dimensions were 100 × 70 × 2 mm. A total of 20 stubs have been tested, as follows: 4 hollow thin welded tubes were tested to axial and eccentric load compression, 4 were filled with ordinary concrete appointed by BO columns, 6 were filled with concrete whose natural sand was completely substituted by a crystallized sand slag designated in this paper by BSI, and 6 were tucked in concrete whose natural sand was partially replaced by a crystallized sand slag called BSII. The main parameters studied are the height of the specimen (300 mm–500 mm), eccentricity of load and type of filling concrete. Based on test results obtained, it is confirmed that the length of the tubes has a considerable effect on the bearing capacity and the failure mode. In all test tubes, fracture occurred by the convex local buckling of steel section due to the outward thrust of the concrete; it was observed that the sand concrete improves the bearing capacity of tubes compounds compared to those filled with ordinary concrete.